Dual-specificity tyrosine-regulated kinases (DYRKs) and cancer: DYRKs in human cancers - Moududee, Sayed A.; You, Zongbing (Serican Journal of Medicine, 2024)
Dual-specificity tyrosine phosphorylation-regulated kinase (DYRK) belongs to the CMGC group of kinases that are named after cyclin-dependent kinases (CDKs), mitogen-activated protein kinases (MAPKs), glycogen synthase kinases (GSKs), and CDC-like kinases (CLKs).  DYRK-related kinases comprise a novel subfamily of protein kinases with unique structural, biochemical, and enzymatic features. In humans, DYRKs phosphorylate a set of proteins and play a critical role in apoptosis, DNA damage repair, cell proliferation, survival, and development. Dysregulation of DYRK protein kinases has been associated with cancer biology. In recent years, several studies have reported some kinase inhibitors affecting cancer development and progression, making them potential therapeutic drugs. However, challenges remain in understanding the molecular mechanisms and roles of each member of DYRK family in cancer initiation and progression. In this review, we will highlight the importance of DYRK kinases in cancer biology.